Optimalisasi Kombinasi Cabang Usahatani untuk Memperoleh Pendapatan Maksimum pada Areal Pekarangan di Unit Pemukiman Transmigrasi (UPT) Cempaka Kecamatan Cempaka Kota Banjarbaru - Nova Regina Tobing; Dolok Saribu; Kamiliah Wilda (Universitas Lambung Mangkurat, 2013)
The small scale integrated farm business is a program introduced in South Kalimantan in order to increase the family income. One of program components is diversifying plant cultivation in the land, including the houseyard. The study intentions are: (1) to describe the cultivation pattern combination in study site; (2) to calculate cost and gross margin of each cultivated plant; and (3) to analyze the optimization of cultivation pattern in order to maximize the income. The study was conducted in UPT Cempaka, Kee. Cempaka, Banjarbaru. A linear programming model was constructed to seek the optimized cultivation pattern. The dominant farming pattem which gives optimum income at the study site is the combination of large chili (cabai besar) and string bean (kacang panjang); and the combination of com and eggplant. The first pattern generates /DR 2. 02 million and /DR 1. 55 million of total revenue and total gross margin, respectively. Meanwhile, the second pattern generates /DR 2.51 million and /DR 2.10 million of total revenue and total gross margin, correspondingly. Based on linear programming model, the first pattern gives the additional gross margin as much as /OR 161,293 and /OR 413,037 for the second one.